2017
DOI: 10.1016/j.whi.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Urban/Rural Differences in Breast and Cervical Cancer Incidence: The Mediating Roles of Socioeconomic Status and Provider Density

Abstract: Background Breast and cervical cancer incidence vary by urbanicity, and several ecological factors could contribute to these patterns. In particular, cancer screening or other sociodemographic and healthcare system variables could explain geographic disparities in cancer incidence. Methods Governmental and research sources provided data on 612 counties in the Surveillance, Epidemiology, and End Results program for rural-urban continuum code, socioeconomic status (SES) quintile, percent non-Hispanic white res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 58 publications
3
42
0
Order By: Relevance
“…Improved health care access and density of primary care physicians in the urban population may explain the urbanrural inequalities in breast cancer incidence [34]. In the Świętokrzyskie Province an increase in the incidence of breast cancer was observed in both groups of patients: urban and rural women.…”
Section: Discussionmentioning
confidence: 95%
“…Improved health care access and density of primary care physicians in the urban population may explain the urbanrural inequalities in breast cancer incidence [34]. In the Świętokrzyskie Province an increase in the incidence of breast cancer was observed in both groups of patients: urban and rural women.…”
Section: Discussionmentioning
confidence: 95%
“…Studies conducted in 1995-2013 in North America showed a similar relationship. Incidence rates, calculated in the analysed period, were higher in urban areas than in rural areas [35,36]. Reasons for these differences include: increased exposure to carcinogenic factors in cities, different city lifestyle, as well as higher fertility rates in women inhabiting rural areas, which reduces the risk of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the incidence pattern for cervical cancer was different, showing a signi cantly higher ASR in "other departments" region, mainly composed of nonmetropolitan and rural areas. It has been reported that women in rural areas may experience barriers to optimal cervical cancer prevention, screening, and treatment, as well as, a higher frequency of risky sexual behaviors (23,24).…”
Section: Discussionmentioning
confidence: 99%